Courage and Holiness - Kieliszek, Zdzisław (Studia Warmińskie, 2012)
In the article the author of “Courage and Holiness”, inspired by the theme of the X Pope Day “Courage of holiness”, which was celebrated in Poland on 10 October 2010, is trying to determine the relationship between the virtue of courage and holiness. In the first part of the discussion analyzed the virtue of fortitude. It has been shown to be patient, persistent and confident to resist evil and generous pursuit of truth, goodness and beauty. Part two is devoted to a reflection on holiness. In light of the studies, it appears as the value of which man realizes, striving for perfection. As indicated in the last part of people’s attitudes, in which the virtue of courage and human desire for perfection coincide with each other. On the basis of analysis the author comes to the conclusion that the process of human striving for holiness is linked to the development of the human virtues of courage.